Nanocarriers applied to the treatment of breast cancer (Research, Society and Development, 2021)
Objective: Evaluate the implications of using nanocarriers in the treatment of breast cancer. Methods: Literature review based in guidelines contained in Preferred Reporting Items for Systematic reviews and Meta-analyses (PRISMA), using these databases: PubMed and Biblioteca Virtual em Saúde, using the key words: “nanoparticles” AND “treatment” AND “breast cancer”. Nineteen articles, written in English, that met the inclusion criteria, were selected. Results: Given the findings on the selected studies, it was perceived a low toxicity on healthy cells and the capacity to direct nanoparticles to the tumor site. Conclusion: The present study allowed the comprehension of the efficacy of de drugs carried on the different nanoparticles, intending to reduce the tumoral cells and minimize the toxicity, with specific liberation of drugs on tumor site.